Social Impact of a Tax Reform : The Case of Ethiopia - Munoz, Sonia; Cho, Stanley (Washington, D.C. : International Monetary Fund, 2003)
This paper provides an assessment of the poverty and social impact of replacing Ethiopia's sales tax with a value-added tax (VAT). The results indicate that this reform has not had a major adverse effect on the poorest 40 percent of the population. The VAT is progressive in its incidence, and the higher revenues brought about by the VAT can provide additional funds for poverty-reducing spending, including primary education. At the same time, there is significant scope for making education spending more pro-poor by increasing the access of low-income households to schools.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet